Improvement Of Soil Chemical Properties In Oil Palm Plantations At Supra Matra Abadi Aek Nabara Estate With The Application Of Empty Oil Palm Bunches - Cherli Putri Indriani Nasution; Fitra Syawal Harahap; Kamsia Dorliana Sitanggang; Ika Ayu Putri Septyani (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Oil palm is a plant greedy for water and nutrients that can ultimately reduce soil conditions both from water and nutrients in the soil; for this reason, it is necessary to improve soil conditions. The application of EFB can be one of the solutions to overcoming the problem. This study aims to determine the Influence of Empty Fruit Bunch on improving the Chemical Properties Of Soil Planted By Oil Palm At Supra Matra Abadi Aek Nabara Estate. This research was conducted at Afdeling III Supra Matra AbadiAek Nabara Estate. This research was conducted for five months. This research method used a Factorial Randomized Block Design (RBD), which consisted of 2 factors. The first factor was soil depth which consisted of 0-15 cm, 15-30 cm, 30- 60 cm, and 60-90 cm. The second factor is the application of empty fruit bunches, which consists of no EFB application (control) and the application of empty fruit bunches: 370 kg/tree. The results showed that giving empty fruit bunches to oil palm plantations can increase soil fertility. The application of EFB affects the pH values of the soil, Potassium, Magnesium, and Calcium. And the depth of the ground, given the application of EFB, negatively affects soil fertility. This means that if the soil's depth increases, soil fertility tends to decrease as well as it should.